2019
DOI: 10.1097/ccm.0000000000003636
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Detection of Brain Cardiolipins in Plasma Is Associated With Outcome After Cardiac Arrest

Abstract: Objective: Brain mitochondrial dysfunction limits neurological recovery after cardiac arrest (CA). Brain polyunsaturated cardiolipins (CLs), mitochondria-unique and functionally essential phospholipids, have unprecedented diversification. Since brain CLs are not present in plasma normally, we hypothesized their appearance would correlate with brain injury severity early after CA and return of spontaneous circulation (ROSC). Design: Observational case-control study Setting: Two medical centers within one city P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“… 32 33 We plan an exploratory investigation into the prognostication accuracy of brain mitochondria-specific CL and CLox, biomarkers developed by our collaborators. 34 35 Finally, families could opt-in for genetic biomarker analysis in which a blood clot remaining from blood biomarker processing procedures is banked for future analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 33 We plan an exploratory investigation into the prognostication accuracy of brain mitochondria-specific CL and CLox, biomarkers developed by our collaborators. 34 35 Finally, families could opt-in for genetic biomarker analysis in which a blood clot remaining from blood biomarker processing procedures is banked for future analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we will include an exploratory analysis of a brain-specific mitochondrial cardiolipin (CL) that when measured in the blood predicted outcome in adults with cardiac arrest and may have utility as a therapeutic target. 19 This manuscript describes the study design, trial management and oversight for the Personalising Outcomes after Child Cardiac Arrest (POCCA) trial.…”
Section: Introductionmentioning
confidence: 99%
“…The pericontusional cortex was isolated from the brain and the lipids were extracted using the folch method. Total phosphate content of the lipids was quantified using the method reported previously (Anthonymuthu et al, 2019). For phospholipid analysis, samples corresponding to approximately 2.5 nanomol of total phosphate were supplemented with the appropriate internal standards (5 picomoles each of phosphatidylcholine (PC) (17:0/17:0), phosphatidylglycerol (PG) (17:0/17:0), phosphatidylinositol (PI) (16:0/16:0), CL (14:0/14:0/14:0/14:0), phosphatidylserine (PS) (17:0/17:0), phosphatidic acid (PA) (17:0/17:0), phosphatidylethanolamine (PE) (17:0/17:0)) and analyzed using LC-MS/MS.…”
Section: Lipid Extraction and Mass Spectrometry Analysismentioning
confidence: 99%
“…Brain tissue has a distinct CL profile based on the number of CL species, acyl chain lengths and degree of unsaturation (Kagan et al, 2015). We recently showed that the appearance of unique brain-type CLs in plasma could serve as a brain-specific marker of mitochondrial/tissue injury in adults after cardiac arrest (Anthonymuthu et al, 2019). Accumulation of three unique CL species [CL(70:3), CL(72:5) and CL(74:7)] correlated with neurological injury severity and functional outcome in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…26 The brain-specific cardiolipin is also detected in plasma samples from patients with brain injury induced by cardiac arrest and from rats subjected to asphyxial cardiac arrest. 27 Furthermore, peroxidized cardiolipin is detected in injured brains, 28 and anticardiolipin antibody is found in the peripheral blood samples of patients with stroke 29 and TBI. 30 An obvious question is whether the cardiolipin detected in these studies are free phospholipid micelles, mitochondrial damage associated molecular patterns (mDAMPs), or exMTs.…”
Section: Traumatic Injured Brains Release Extracellular Mitochondriamentioning
confidence: 99%